Pengaruh Profitabilitas, Ukuran Perusahaan, KinerjaLingkungan, dan Leverage terhadap Pengungkapan IslamicSocial Reporting - Wulandari, Fitri; , Dr. Fatchan Ahyani, SE., M.Si (2015)
ISR is a social performance reporting standards the companies based on sharia. This index was developed with a base of reporting based AAOIFI standards are then developed by each subsequent researchers. The aim of this study was to test the effect of profitability, company size, environmental performance and leverage on the disclosure of Islamic Social Reporting. Population in this study are all companies listed in the Daftar Efek Syariah during two periods in 2014. The sample was determined by purposive sampling technique in order to obtain a total sample of 48. The data were analyzed using descriptive statistics and multiple linear regression analysis. The results showed that the profitability and size of the company's significant effect on the disclosure of Islamic Social Reporting. Environmental performance and leverage while no significant effect on the disclosure of Islamic Social Reporting.